The Influence of Soil Characteristic Changes on Erosion Rates Based on the Universal Soil Loss Equation (USLE) Method - Idah Andriyani; Yaumil Zahro Fadila (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Soil erodibility is a major factor contributing to soil erosion as well as the intensity of erosion rates. This study aims to validate soil erodibility values based on soil type maps through field measurements of erosion hazard level (EHL) within the Antrokan Sub-watershed area, Jember. Input data included digital maps comprising rainfall data (from 2004 to 2019), soil types, land use allocation, and Digital Elevation Model (DEM). Erosion rate was calculated using the USLE model, which was executed in two steps: (1) processing and interpreting erosion variables (R, K, LS, CP), and (2) calculating and classifying soil EHL. Field measurements indicated that soil erodibility value (K) is higher as compared to the value derived from the soil type maps. This discrepancy impacts the predicted erosion rate, where using measured K values resulted in the severe EHL category, with erosion rate of 1131 t.ha–1.y–1, while using K values based on soil type maps produced erosion rate of 432.2 t.ha–1.y–1, categorized as moderate level. In this sense, validation of soil erodibility data is important for predicting erosion rate using USLE method. In conclusion, the soil conservation implementation to reduce K values is necessary in the Antrokan Sub-watershed area Keywords: Erodibility, Erosion hazard level, Nomograph, Soil type, USLE.